ANALISIS KUALITAS SINYAL 4G DENGAN METODE WALK TEST MENGGUNAKAN SOFTWARE TEMS DI AREA INDOOR - Adenia, Candra; Partiansyah, Fakhriy Hario; Mustofa, Ali (Jurnal Mahasiswa TEUB, 2024)
Abstract- The current cellular network in Indonesia has reached the fifth generation (5G). The uneven distribution of the fifth generation in Indonesia leads the Indonesian population to still rely on the previous generation, namely 4G. According to a survey conducted among Electrical Engineering students at Brawijaya University, 73,5% of students still use 4G cellular networks, with Telkomsel being the dominant operator at 57, 4%. Some Electrical Engineering students have reported issues, specifically in Building C, experiencing blank spots for Telkomsel's 4G network. Based on the issues mentioned above, this research aims to conduct a walk test in the indoor area of Building C, Electrical Engineering Department, Faculty of Engineering, Brawijaya University, using TEMS Pocket software. The objective is to assess the quality of the fourth-generation (4G) cellular network in the indoor area of Building C, utilizing a walk test method, and to understand the characteristics of cellular communication indoors. The research methodology begins with a literature review, followed by the walk test, data processing, analysis of the walk test results, and concluding with findings and recommendations. Parameters such as Received Signal Referenced Power (RSRP), Received Signal Referenced Quality (RSRQ), Received Signal Strength Indicator (RSSI), and Signal to Interference plus Noise Ratio (SINR) are employed to evaluate the quality of the Telkomsel 4G network. The research findings indicate that the majority of test points foreach parameter in the indoor area of Building C exhibit good signal quality based on Key Performance Indicators. However, some test points show poor quality due to obstacles in the area, leading to multipath interference that affects the Signal-to-Noise Ratio (SNR) and subsequently influences signal quality.Keywords: walk test, signal quality, 4G, multipath